Unfounded, Cleared, or Cleared by Exceptional Means: Sexual Assault Case Outcomes From 1999 to 2014 - Venema, Rachel M. (Journal of interpersonal violence, 2021)
Sexual assault is a highly underreported crime with even fewer cases proceeding to the point of charges and prosecution, suggesting that sexual assault victims have less opportunity for legal justice than other crime victims. Case attrition may, in part, be due to negative attitudes and rape myth acceptance (RMA) in police decision making. Yet, little attention has been paid to examining the evidentiary and extralegal factors surrounding the case that contribute to police decision making and case outcomes through examination of police case files. This examination is necessary to address the issue of differential processing of sexual assault cases in the criminal justice system. This study uses police data of sexual assault case files from 1999 to 2014 (N = 23,525) to examine the assault, victim, and detective characteristics that contribute to case outcomes of unfounded, cleared, and exceptionally cleared through arrest and victim refusal to prosecute. Logistic regression models tested 15 years of reported sexual assault data from one large police department and found that elements that correspond with RMA were predictive of unfounded, cleared, and exceptionally cleared case decisions, providing further indication that officers consider evidentiary but also extralegal factors in decision making. Overall, results support previous contentions that sexual assault victims have unequal access to legal justice, particularly victims possessing demographic and assault characteristics that do not align with stereotypical notions of rape. Implications for future research and policing practices are discussed.